2015
DOI: 10.1002/2015ja021528
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation and loss of signal lock from poleward moving auroral forms in the cusp ionosphere

Abstract: We present two examples from the cusp ionosphere over Svalbard, where poleward moving auroral forms (PMAFs) are causing significant phase scintillation in signals from navigation satellites. The data were obtained using a combination of ground‐based optical instruments and a newly installed multiconstellation navigation signal receiver at Longyearbyen. Both events affected signals from GPS and Global Navigation Satellite System (GLONASS). When one intense PMAF appeared, the signal from one GPS spacecraft also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 112 publications
(265 reference statements)
7
87
0
1
Order By: Relevance
“…The dayside events show higher occurrence and are located at higher latitude (|MLAT| ≥ 70 • ), and they are possibly collocated with the cusp region (Reiff et al, 1977) in the Southern Hemisphere; while the nightside events prefer to appear at lower latitudes (between 50 • ≤ |MLAT| ≤ 60 • ) and are possibly collocated with the auroral oval (Feldstein, 1963;Akasofu, 1966) in both hemispheres. Scintillations on the radio wave signals have already been reported at high latitudes (e.g., Martin and Aarons, 1977;Rino et al, 1978;Aarons et al, 1997), and evidence showed that they are highly related to these high-latitude irregularities (e.g., Meeren et al, 2015;Oksavik et al, 2015;Jin et al, 2015;Clausen et al, 2016). The GPS signal loss of Swarm satellites at high latitudes is also believed to be caused by the irregularities.…”
Section: Gps Signal Loss Event Detectionmentioning
confidence: 94%
See 1 more Smart Citation
“…The dayside events show higher occurrence and are located at higher latitude (|MLAT| ≥ 70 • ), and they are possibly collocated with the cusp region (Reiff et al, 1977) in the Southern Hemisphere; while the nightside events prefer to appear at lower latitudes (between 50 • ≤ |MLAT| ≤ 60 • ) and are possibly collocated with the auroral oval (Feldstein, 1963;Akasofu, 1966) in both hemispheres. Scintillations on the radio wave signals have already been reported at high latitudes (e.g., Martin and Aarons, 1977;Rino et al, 1978;Aarons et al, 1997), and evidence showed that they are highly related to these high-latitude irregularities (e.g., Meeren et al, 2015;Oksavik et al, 2015;Jin et al, 2015;Clausen et al, 2016). The GPS signal loss of Swarm satellites at high latitudes is also believed to be caused by the irregularities.…”
Section: Gps Signal Loss Event Detectionmentioning
confidence: 94%
“…The low-latitude irregularities derived from TEC measurements show a typical orientation dependence, which is strongest when the corresponding GNSS satellite is westward of the receiver with elevation angles of about 40-60 • (Park et al, 2015), and TEC gradients at high latitudes are also found to be strongest when the line of sight (LOS) between the receiver and GNSS satellites is most aligned with the ionospheric L-shell surface (Park et al, 2017). Therefore, we also checked if a similar orientation dependence can be found for the Swarm GPS signal loss events.…”
Section: Orientation Dependence Of Gps Signal Lossmentioning
confidence: 99%
“…Strong amplitude scintillation at L-band are rare at polar latitudes (Prikryl et al, 2010(Prikryl et al, , 2011 due to which space weather researchers have a common opinion that the σ φ is a more reliable scintillation index than the S 4 for the polar ionosphere. Poleward moving auroral forms (PMAFs) and their dependence on IMF (interplanetary magnetic field) have been discussed by Rinne et al (2007Rinne et al ( , 2010 and Oksavik et al (2011Oksavik et al ( , 2015, and references therein. These research studies have reported that PMAFs causes severe phase scintillation and temporary loss of lock in the navigation satellite signals.…”
Section: Introductionmentioning
confidence: 99%
“…Still the long time duration (3-5 h) auroral emissions neither were studied nor characterized based on their boundary movement. Many researchers have attempted ionospheric scintillation associate to the dayside as well as nighside auroral emission (e.g., Jin et al, 2015Jin et al, , 2016Jin et al, , 2017Oksavik et al, 2015;Prikryl et al, 2015;van der Meeren et al, 2015) but, the ionospheric scintillation response on the GNSS signal caused at the poleward as well as equatorward edge of the auroral emission boundary is poorly understood. Feldstein and Galperin (1985), Lyons et al (2000), Zesta et al (2002); and references therein; have discussed the structure of the auroral emission in really great details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation